The Impact of Legal Policies on the Enforcement of Human Rights in Indonesia - Baan, Bram B; Ginting, Grenaldo; Putra, Irman; Lubis, Arief Fahmi; Miharja, Marjan (Inovasi Pratama Internasional. Ltd, 2025)
The realisation of human rights constitutes a crucial element in the establishment of social justice and the safeguarding of individual dignity. In Indonesia, legal policies pertaining to human rights have evolved since the advent of the reform era, with the advent of numerous regulations and the establishment of institutions dedicated to the protection of human rights. This research employs a literature study method to analyze the impact of legal policies on human rights enforcement in Indonesia. The study analyzes relevant regulations, legal precedents, and academic literature to identify challenges and opportunities in the implementation of human rights policies. The findings reveal that, although Indonesia has witnessed significant advancements in the legislative realm, persistent challenges persist in ensuring consistent policy implementation. These obstacles encompass deficiencies in law enforcement, shortcomings in institutional competence, and the influence of political dynamics upon policy implementation. Hence, enhancements in legal governance and the fortification of human rights institutions are indispensable to guarantee the effective enforcement of human rights in Indonesia.